SISTEM INFORMASI PROMOSI DAN PENJUALAN KERAJINAN SULAMAN BERBASIS WEB PADA SULAMAN INDAH MAYANG PARIAMAN - Nelfira, Nelfira; Putri, Nency Extise; Yuni, Via Rahmai (Rang Teknik Journal, 2019)
This reseach was conducted at the handycrafts Sulaman Indah Mayang Pariaman. Sulaman Indah Mayang is a bussiness that sells various kinds of minang embroidered crafts. The effort craft Sulaman Indah Mayang still use conventional way in processing sales data and do promotion.  For  that  required  an  information  system  that  will  assist  in  the  process  of  promotion  and  sales. Information system application of promotion and sale of web based embroidery craft developed using PHP programming language and MySql as database. Application design using object oriented methodology with UML design tool. The end result of this research is the creation of application of Information System Promotion and Web- Based Sales that can help Sulaman Indah Mayang in the process of promotion and sales.